Two monologues do not make a dialogue: the need for medical specialty–specific communication workshops: population-based study. Issue 1 (21st March 2019) - Palocaren, Jeeji; Puthuparampil, Renjith Raj; Thalappillil, Celine Mathew
Abstract : Aim: Increasing attacks on healthcare personnel in India have highlighted the need for improved communication between staff and patients. Currently, communication skill workshops target doctors and nurses, overlooking a key player relevant to patient satisfaction—allied health professionals (henceforth, AHPs). This study evaluates the impact of communication skills training for diagnostic laboratory and blood bank personnel on patient satisfaction scores. Method: The impact of communication workshop for AHPs was tested through pre-workshop and post-workshop questionnaires to participants that tested how they handle communication with patients. Additionally, participants were also administered the questionnaire 4 months after the workshop to test knowledge retention. In parallel, the change in patient satisfaction towards AHPs was assessed by a pre-workshop and post-workshop patient survey. Results: Participants experienced a statistically significant improvement in communication skills, as measured by the pre-workshop and post-workshop questionnaires. This coincided with a significant increase in patient satisfaction scores after the workshop, as indicated by the patient satisfaction survey. The difference in communication skills scores between experienced and inexperienced personnel showed a marked decrease after the workshop, suggesting that such workshops can help inexperienced workers 'catch up' with more experienced workers. However, scores of all participants showed a statistically significant decrease after 4 months, suggesting that the use of such workshops can be enhanced through periodic refresher courses. Conclusion: Communication workshops for AHPs can play a crucial role in improving patient–hospital relations. These workshops can also help standardise services by bridging communication skill differences between experienced and inexperienced staff.